Selection of Infectious Waste Storage from Disposable Personal Protective Equipment in the Era of the Covid-19 Pandemic (Universitas Negeri Semarang, 2022)
Disposable personal protective equipment (PPE) waste is one type of waste that can be found in public facilities such as stations. Improper storage can create new impacts and contaminate waste that does not have the same properties. The purpose of this study is to analyze various alternatives to the best disposable personal protective infectious waste disposal facilities. The method used in the selection of alternatives is the Analytical Hierarchy Process (AHP). The three alternatives provided based on the literature review are hand sanitizer (A1), ultraviolet lamp (A2), and disinfectant spray (A3). The criteria used in the selection of alternatives are virus removal in storage, equipment maintenance, and electricity consumption costs. Analysis of the weight of the criteria shows that the highest weight is in the criteria for virus removal in the container. The results of the weight assessment show that alternatives A2 and A3 have values of 0.499 and 0.406, respectively. The use of virus removal tools is more important than the addition of hand sanitizer facilities which only have a weight of 0.095.